Clinical impact of surgical treatment for the spontaneously ruptured resectable hepatocellular carcinoma: A single institution experience. Issue 35 (2nd September 2022) - Xu, KangHe; Ryu, Dong Hee; Choi, Jae-Woon; Choi, Hanlim; Kim, Dae Hoon; Lee, Taek-Gu; Kim, Myung Jo; Park, Sungmin; Yoo, Kwon Cheol
Abstract : Spontaneously ruptured hepatocellular carcinoma (srHCC) is a fatal complication of hepatocellular carcinoma (HCC). In addition, emergency treatment is frequently fraught with difficulties. This study aimed to investigate the prognosis and recurrence pattern in patients undergoing hepatectomy for the srHCC. This retrospective study included 11 patients with srHCC treated using either emergency hepatectomy or emergency transarterial embolization (TAE) followed by staged hepatectomy between January 2015 and December 2019. The patients visited the emergency room because of a sudden rupture of HCC without being diagnosed with HCC. We analyzed the prognosis, recurrence rate, and survival in these patients after hepatectomy. Four of the 11 patients in this study were classified as Child–Pugh class A and 7 as Child–Pugh class B. Nine patients visited for sudden onset of abdominal pain, and 2 for sudden onset of shock. The median hemoglobin level at the time of the visit was 11.5 g/dL (interquartile range: 9.8–12.7). Five patients underwent one-stage hepatectomy and 6 underwent emergency TAE hemostasis followed by staged hepatectomy. Median overall survival and recurrence-free survivals were 23 and 15 months, respectively. Recurrence occurred in 7 patients (4 in the one-stage group and 3 in the staged group). Among patients with recurrence, 6 had intrahepatic recurrence and 3 peritoneal metastases. Patients with srHCC who undergo staged hepatectomy can achieve a relatively good prognosis. The most common sites of recurrence after hepatectomy are intrahepatic and peritoneal. Peritoneal metastases are more likely to occur after one-stage hepatectomy.